Penguatan Peran Orang yang Dianggap Penting dalam Penerapan Gizi Seimbang pada Remaja di Tohudan Wetan Colomadu: Strengthening the Role of People Who are Considered Important in the Implementation of Balanced Nutrition in Teenagers in Tohudan Wetan Colomadu - Kusumaningrum, Tanjung Anitasari Indah; Madona, Ade; Saputra, Oktavian Reno; Seviani, Kiky Firda; Meyzwari, Fioriska Putri; Widyantoro, Claristha Kristya; Rini, Novyanti Setiyo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Adolescents in Tohudan Wetan have insufficient knowledge about balanced nutrition. Teenagers often do not pay attention to the nutritional intake they consume and like to eat fast food. Teenagers also often follow trends in the type of food they consume. This service aims to provide information to teenagers about healthy food, balanced nutrition, the benefits of consuming balanced nutritious food, and the impact of consuming junk food. This service will be carried out online in 2021. The targets of this service are 15 teenagers and 3 friends who are considered important by the 15 teenagers. This activity was carried out by providing information regarding types of healthy food as well as giving messages to three people who were considered important by teenagers to inform and remind teenagers to continue consuming balanced nutritious food. Through education and strengthening the role of people who are considered important in implementing balanced nutrition, the results showed that there was an increase in teenagers' knowledge regarding balanced nutritional consumption patterns and there were teenagers who succeeded in reducing their consumption of unhealthy foods such as junk food. The importance of support from people who are considered important makes them more committed to changing behavior because the support of friends becomes a reinforcing factor for behavior change.